2018
DOI: 10.1186/s12950-018-0186-7
|View full text |Cite
|
Sign up to set email alerts
|

CXCR-4 expression by circulating endothelial progenitor cells and SDF-1 serum levels are elevated in septic patients

Abstract: BackgroundEndothelial progenitor cell (EPC) numbers are increased in septic patients and correlate with survival. In this study, we investigated, whether surface expression of chemokine receptors and other receptors important for EPC homing is upregulated by EPC from septic patients and if this is associated with clinical outcome.MethodsPeripheral blood mononuclear cells from septic patients (n = 30), ICU control patients (n = 11) and healthy volunteers (n = 15) were isolated by Ficoll density gradient centrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Soluble factors such as VEGF and Ang-2 mediate the mobilization from bone marrow through the activation of metalloproteinases and upregulation of adhesion molecules [3,[25][26][27]. We have previously demonstrated that plasma levels of VEGF and Ang-2 are increased in septic patients and correlate with the number of EPC [28,29]. Similar findings were shown for Ang-2 in ARDS [30,31].…”
Section: Discussionsupporting
confidence: 56%
“…Soluble factors such as VEGF and Ang-2 mediate the mobilization from bone marrow through the activation of metalloproteinases and upregulation of adhesion molecules [3,[25][26][27]. We have previously demonstrated that plasma levels of VEGF and Ang-2 are increased in septic patients and correlate with the number of EPC [28,29]. Similar findings were shown for Ang-2 in ARDS [30,31].…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, BM-EPCs sheets formed tubular structures in the in vitro model of angiogenesis. SDF-1α, which mediates many disparate processes exclusively via a single cell surface receptor known as chemokine receptor CXCR4, has been found to promote BM-EPC cell mobilization into the ischemic site, where they promote repair by inducing vasculogenesis and secreting bene cial paracrine factors [8,21,22]. Following veri cation of the migration potential of EPCs, the data from the present study indicated that a dose of 10 ng/ml SDF-1α is the optimal concentration for BM-EPC cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Tie-2 receptors which control the mobilizations of EPCs, are controlled by two legends angiopoietin I (Ang I) and angiopoietin II (Ang II) (Siavashi et al, 2016), Ang I induced and stabilized tube-like structures via EPC intracellular Tie2-FAK-AKT complex and subsequent changes in pp38, pSAPK/JNK, and phosphorylated extracellular signal-regulated kinases mediated Mitogenactivated protein kinases activation (Moon et al, 2015), However, The density of the cells came by activation of CD34 is increased by upregulation of Ang II (Siavashi et al, 2016) as well as it was showed to activate mobilization of EPCs in ischemic condition by exocytosis (Kuo et al, 2008). In addition, it was found a positive correlation of VEGF, Ang II and SDF-1 with EPC levels in septic patients indicates an impact of those factors on mobilization of EPC from the bone marrow during sepsis (Patry et al, 2018). angiogenesis and blood flow in the rat critical limb ischemia area (Chua et al, 2013).…”
Section: R a F Tmentioning
confidence: 93%